Peran Tradisi Poda Na Lima Dalam Pembentukan Karakter Siswa Di Sekolah Dasar - Ahmad Fauzi Pulungan; Mutiah Lubis; Anggi Julianti; Atika; Nurrizki Mustamirun (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study to analyze the role of the Poda Na Lima tradition in shaping the character of elementary school students thorough a literature review approach. Poda Na Lima is a local wisdom of the Mandailing community that embodies five fundamental moral principles as guidance for social conduct and educational values. This research employs a library research method by collecting and analyzing relevant literature, including Mandailing cultural texts, academic journals, and scholarly articles on character education. The discussion focuses on the relevance of Poda Na Lima in fostering the values of responsibility, honesty, and respect and obedience toward teachers and parents among elementary school students. The findings indicate that Poda Na Lima holds significant potential as a normative foundation for character formation, as its values align with the objectives of national character education. Thus, this tradition is highly relevant to be integrated into local wisdom-based learning as an effort to strengthen character education from an early age.